Rancang Bangun Aplikasi Penentuan Harga Pokok Produksi Pada UMKM Burhan Foam - Ariyanti, Fitri Dwi; Widodo, Arifin Puji; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Micro businesses, small and medium enterprises (SMEs) Burhan Foam is a business that manufacture or production of the folding mattresses, pillows and bolsters that produce based on customer orders.During this time, SMEs have a profit decline with increased order in some types of mattresses.And also have a decreased orders for some other type of mattress. This is because SMEs do not have a mechanism to calculate the exact cost of production.SMEs do not calculate the overhead costs (operating the factory) into the calculation of the production cost.These conditions make the specified price is too high (Over Budget) or too low (Underbuget).From these problems, the author created design applications determining the cost of production in SMEs Burhan Foam using Job Order Costing (cost of the order).Which generates reports raw material costs, labor costs report indirect, fixed factory overhead expense reports, report variable factory overhead costs, and report the cost of production.Other than that, the system also generates reports bookings per month.Based design applications made and trials that have been done, found that the cost of production information needed by SMEs and the details of the element of cost of production have been found.